Dynamics of the Schrödinger–Langevin equation. (18th February 2021) - Chauleur, Quentin
Abstract: We consider the nonlinear Schrödinger–Langevin equation for both signs of the logarithmic nonlinearity. We explicitly compute the dynamics of Gaussian solutions for large times, which is obtained through the study of a particular nonlinear differential equation of order 2. We then give the asymptotic behavior of general energy weak solutions under some regularity assumptions. Some numerical simulations are performed in order to corroborate the theoretical results.